Perlindungan Hukum Bagi Konsumen Dalam Transaksi Jual Beli Online (E-Commerce) - Agung Maghfira Mubila; Ikhsan Fadillah; Helfira Citra (GLOBAL SCIENTS PUBLISHER, 2025)
The development of digital technology has transformed the consumption patterns of modern society by introducing an internet-based trade system known as e-commerce. This transaction model provides ease and speed in the buying and selling process, but it also harbors various risks for consumers. Consumers are often harmed by the actions of irresponsible business actors, such as the delivery of goods that do not match, delays, and even fraud. This study aims to analyze the legal protection of consumers in e-commerce transactions based on the applicable laws and regulations in Indonesia. This research uses a normative jridical method, with an approach to legislation, legal literature, and case studies. The results show that although consumer protection has been explicitly regulated in various regulations such as Law No. 8 of 1999 concerning Consumer Protection, the ITE Law, and Government Regulation No. 80 of 2019 concerning. Electronic Trading Systems, however, its implementation still faces significant challenges both from technical, legal, and public awareness perspectives. This analysis provides an in-depth overview of legal protection efforts as well as recommendations that can be implemented to enhance the effectiveness of consumer protection in the future.